Semi-domesticated reindeer avoid winter habitats with exotic tree species Pinus contorta - Horstkotte, Tim; Sandström, Per; Neumann, Wiebke; Skarin, Anna; Adler, Sven; Roos, Ulrika; Sjögren, Jörgen (2023)
The introduction of exotic tree species can have profound effects on the native environment, including habitat use and movement patterns of animals, as well as becoming a management challenge for other land users. Here, we used GPS data from reindeer (Rangifer tarandus) and remote sensing measurements of lichen cover and soil moisture to assess the effects of the exotic lodgepole pine (Pinus contorta) on reindeer husbandry by the Indig-enous S ' ami in northern Sweden. We used locational data from 67 reindeer for three winters to analyze their habitat selection at the second-order selection (placement of home range in the landscape) and third-order se-lection (selection of sites within the home range) in relation to land cover class, terricolous lichen cover as measure of winter forage abundance, topographic features, and distance to roads. We also analyzed remotely sensed abundance of lichens in different forest types, and the association between these forest types and soil moisture as measure of suitability as lichen habitat. Compared to native P. sylvestris, we found that reindeer avoided stands with P. contorta where trees were higher than three meters. If P. contorta was the dominant tree species, reindeer were 60 % less likely to select these stands compared to stands with P. sylvestris, and 40 % less likely if P. contorta was less dominant at both orders of selection. We also found that reindeer selected areas with higher lichen cover. Lichen cover was lower in P. contorta stands compared to stands of the native P. sylvestris, even though P. contorta occurred mainly on dry soils usually favorable for terricolous lichens. We conclude that planting P. contorta on soils suitable for terricolous lichens is likely to reduce forage availability for reindeer and turn habitats earlier preferred by reindeer into avoided habitat, resulting in an overall reduction of winter grazing grounds. The effects of stands with P. contorta, albeit covering a comparatively small percentage of the reindeer husbandry area, need ...